Pengaruhkompensasi dan kondisi kerja terhadap kepuasan kerja karyawan PT. Sentra Karya Cahaya Raya di Pekanbaru - Andri Susanto; Machasin '; Samsir ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The study was conducted in PT. Sentra Karya Raya Pekanbaru Light which is a general trade contractors. The purpose of this study was to analyze the effect of compensation and working conditions on employee job satisfaction. The study population was the entire staff of about 63 employees who conducted the census. Analysis of data using multiple linear regression analysis using SPSS 17 for windows. The results showed that compensation and a significant positive effect on job satisfaction. In contrast, although the working conditions had a positive effect but not significant impact on job satisfaction. Job satisfaction of 44.3 % can be explained as the variation that occurs in variable compensation and working conditions. Recommendation that can be given is that management adjusts the amount of receipts in the form of compensation to the employees base salary and incentives in line with the applicable regulations, as well as holding a pension plan and budget for employee recreation. Working conditions by increasing the harmonious relationship between employees and security need to be dikondusifkan back.Keywords : Compensation , Working Conditions and Job Satisfaction